2018
DOI: 10.1159/000494225
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Endometrial Stromal Sarcoma - a Review

Abstract: Like other uterine sarcomas, low-grade endometrial stromal sarcomas (LG-ESS) are a very rare tumor entity. In the past, research studies therefore discussed the various different types of the disease in combination. In addition, the classification of endometrial stromal tumors presented difficulties for quite some time so that in earlier studies it was not always possible to precisely distinguish between LG-ESS, high-grade endometrial stromal sarcoma, and undifferentiated uterine sarcoma. For LG-ESS, surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 64 publications
0
63
0
5
Order By: Relevance
“…This disease was also known to affect females in their 50s to 60s while our data showed that patients with stage I LGESS were initially diagnosed in their 40s . Approximately 30–50% of patients with ESS show atypical symptom of abnormal uterine bleeding . Positive lymph nodes are usually associated with extrauterine metastasis, deep myometrial invasion and lymphvascular space invasion, which also could enlarge nodes .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This disease was also known to affect females in their 50s to 60s while our data showed that patients with stage I LGESS were initially diagnosed in their 40s . Approximately 30–50% of patients with ESS show atypical symptom of abnormal uterine bleeding . Positive lymph nodes are usually associated with extrauterine metastasis, deep myometrial invasion and lymphvascular space invasion, which also could enlarge nodes .…”
Section: Discussionmentioning
confidence: 64%
“…9 Approximately 30-50% of patients with ESS show atypical symptom of abnormal uterine bleeding. 13 Positive lymph nodes are usually associated with extrauterine metastasis, deep myometrial invasion and lymphvascular space invasion, which also could enlarge nodes. 15,23 Therefore, the benefits of systematic LND remain controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they have better prognosis than other uterine sarcomas [17]. In most cases, the recurrence period varied from 3 months to 23 years, with a median interval of 3 years [18]. Long-term follow-up is critical due to the high longterm recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the most frequently reported sites of metastases of the LG-ESS are the vagina, pelvis, and peritoneal cavity. Cardiac metastases are rare because ESS commonly spreads through the lymph nodes and venous system [6].To our knowledge, 18 LG-ESS patients with heart involvement have been reported to date, and their clinical characteristics are summarized as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%